2020
DOI: 10.1097/rhu.0000000000001552
|View full text |Cite
|
Sign up to set email alerts
|

Incidence Rates of Interstitial Lung Disease Events in Tofacitinib-Treated Rheumatoid Arthritis Patients

Abstract: Background/Objective Tofacitinib is an oral Janus kinase inhibitor for the treatment of rheumatoid arthritis (RA). Interstitial lung disease (ILD) is an extra-articular manifestation of RA. We investigated incidence rates of ILD in patients with RA, receiving tofacitinib 5 or 10 mg twice daily, and identified potential risk factors for ILD. Methods This post hoc analysis comprised a pooled analysis of patients receiving tofacitinib 5 or 10 mg twice daily or placebo from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 52 publications
2
21
0
1
Order By: Relevance
“…Tofacitinib, also an oral Janus kinase inhibitor, reported a similar incidence rate of 0.18 per 100 PYE for non-infectious chronic ILD at both doses of 5 mg and 10 mg daily. In the tofacitinib analysis, the median onset time of ILD from the starting of treatment in RA patients was 1144 days, also comparable with our current analysis (range, 60-1740 days) [21]. JAK inhibition has been associated with infections mainly of the upper respiratory and urinary tract [22].…”
Section: Discussionsupporting
confidence: 86%
“…Tofacitinib, also an oral Janus kinase inhibitor, reported a similar incidence rate of 0.18 per 100 PYE for non-infectious chronic ILD at both doses of 5 mg and 10 mg daily. In the tofacitinib analysis, the median onset time of ILD from the starting of treatment in RA patients was 1144 days, also comparable with our current analysis (range, 60-1740 days) [21]. JAK inhibition has been associated with infections mainly of the upper respiratory and urinary tract [22].…”
Section: Discussionsupporting
confidence: 86%
“…Even less is understood about Janus kinase inhibition in patients with bronchiectasis. While post hoc analysis of phase 2, 3 and 3b/4 clinical trials indicates that the de novo incidence of interstitial lung disease is low in patients with rheumatoid arthritis treated with JAKi [21]; to our knowledge, no study has yet examined the pulmonary tolerance and safety of JAKi in those with existing ILD or bronchiectasis. The current study sought to address this important clinical scenario, by comparing time to respiratory events in patients receiving JAKi with patients receiving the current, best-practice medication for this clinical cohort, rituximab.…”
Section: Discussionmentioning
confidence: 98%
“…A post hoc analysis on 7061 RA patients receiving tofacitinib from clinical trials and long-term extension studies reported an incidence rate for ILD with both tofacitinib doses of 0.18 per 100 patient-years [ 17 ].…”
Section: Discussionmentioning
confidence: 99%